Strategi Penanaman Nilai-Nilai Anti Korupsi Pada Mahasiswa - Achmad Asfi Burhanuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Corruption is one of the serious problems faced by the people and the State of Indonesia, therefore it requires extraordinary efforts to eradicate it. Efforts to eradicate corruption do not only focus on efforts to take action against corruptors (repressive efforts), but also focus on efforts to prevent corruption (preventive efforts). Anti-corruption education is a preventive effort that can be done for the younger generation, through 3 channels, namely: 1) education on campus which is called formal education, 2) education in the family environment called informal education, and 3) education in the community called education. with non-formal education. Anti-corruption education must integrate the domains of knowledge (cognitive), attitudes and behavior (affective), and skills (psychomotor). Anti-corruption values ​​must be instilled, lived and practiced by every Indonesian from an early age to college, if necessary, long life education, meaning that anti-corruption values ​​become breath at all times, by instilling anti-corruption education from an early age to students so that students have a soul anti Corruption. This anti-corruption spirit will become a stronghold for them not to commit acts of corruption when they grow up. Therefore, the program launched by the Ministry of Education and Culture in collaboration with the KPK should be realized immediately. Strategies for handling corruption or efforts to prevent corruption can be carried out through educational institutions or campuses, namely by instilling anti-corruption values ​​which include honesty, caring, independence, discipline, responsibility, hard work, simplicity, courage, justice. Anti-corruption values ​​on campus are carried out in various steps, namely by: Integrated models in courses, civilizing models, habituation of values ​​in all activities and campus atmosphere, models outside of learning through extracurricular activities and combined models.